2011
DOI: 10.1159/000323837
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Pelvic Arteriovenous Malformation Presenting with Urinary Retention: A Case Report

Abstract: Objective: To report a case of congenital pelvic arteriovenous malformation (pAVM) with urinary retention. Clinical Presentation and Intervention: A 39-year-old male patient presented with inability to void urine for 8 h. He did not have a history of dysuria or fever, but had increasing urinary frequency and difficulty in voiding over 2 years. Examination revealed a suprapubic mass without external signs of vascular anomaly. A huge, soft, irregular, non-pulsating mass was felt rectally. This mass did not disap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…pAVMs are uncommon vascular entities, which are classified as congenital or acquired which are secondary to trauma, operation, or pregnancy. 1,2 Both patients in this study reported no history of trauma or operation of pelvic organs; however, MRI performed before the prostate biopsy demonstrated AVMs. Thus, these lesions were classified as congenital pAVMs.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…pAVMs are uncommon vascular entities, which are classified as congenital or acquired which are secondary to trauma, operation, or pregnancy. 1,2 Both patients in this study reported no history of trauma or operation of pelvic organs; however, MRI performed before the prostate biopsy demonstrated AVMs. Thus, these lesions were classified as congenital pAVMs.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, these lesions were classified as congenital pAVMs. pAVMs may present with pelvic pain, hematuria, dysuria, erectile dysfunction, heart failure, and massive bleeding during transurethral resection of the prostate . Both patients had been asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also cases described in literature in which AVMs are known to damage part of the sacrum and, by pressing on the nerve, cause sciatic neuralgia [5]. Hammad [6] describes a case of pAVM manifested by ischuria resulting from pressure on the bladder.…”
Section: Discussionmentioning
confidence: 99%